Banthưk lap NGOs - Chatchawān Th̨̄ongdīl̄œt (Khana Kammakān Prasān Ngān ʻOngk̨̄on Phatthanā ʻĒkkachon Phāk N̄ưa : Sathāban Songs̄œm Kānrīanrū ph̄ưa Kānphatthanā thī Yangȳưn, Mūnnithi Phatthanā Phāk N̄̄ưa, 2000)
Contributed articles on Non-government organizations in Northern Thailand.